Early warming stress on rainbow trout juveniles impairs male reproduction but contrastingly elicits intergenerational thermotolerance - Butzge, Arno Juliano [UNESP]; Yoshinaga, Tulio Teruo; Acosta, Omar David Moreno; Fernandino, Juan Ignacio; Sanches, Eduardo Antônio [UNESP]; Tabata, Yara Aiko; de Oliveira, Claudio [UNESP]; Takahashi, Neuza Sumico; Hattori, Ricardo Shohei (Springer Nature, 2021)
The exposure of adult fish to warm or high temperatures is known to impair reproduction, yet the long-term reproductive impacts for treatments at early life are not well clarified. This study aimed to evaluate the effects of warm temperature (WT) during juvenile stage on gonad maturation, gamete quality, and offspring thermotolerance in rainbow trout. While the comparison of basic reproductive parameters in WT females did not reveal any kind of impairment, many WT males showed an atrophied, undeveloped gonad, or a smaller testis with lower milt volume; sperm quality parameters in WT males and deformity rates in the respective progeny were also highly affected. However, despite of such negative effects, many of the remaining progeny presented better rates of survival and growth when exposed to the same conditions as those of parental fish (WT), suggesting that thermal stress in parr stage males elicited intergenerational thermotolerance after a single generation. The present results support that prolonged warming stress during early life stages can adversely affect key reproductive aspects, but contrastingly increase offspring performance at upper thermal ranges. These findings have implications on the capacity of fish to adapt and to cope with global warming.